Determining factors of informal employment in the Moquegua region - Wilson Cañapatana Castillo (2019)
Informal employment has become a social problem, since a large part of the population does not have access to the most favorable working conditions. Informal employment leads to damages for the economic development and welfare of society, since it makes possible the lack of access to labor benefits, such as access to health insurance, perks and vacations. In this paper, a logit model of nonlinear probability is presented, which is one of the most used models to determine the most important factors in binary response variables. In this sense, the purpose of this work is to contribute with the local and scientific community by identifying the factors that determine informal employment in the region. The results of this work indicate that being a woman, belonging to the services, commerce, construction or industry sector, having secondary or higher education, being young and coming from the rural area are characteristics that determine the probability of obtaining informal employment in the region Moquegua.